An optimized negative-staining protocol of electron microscopy for apoE4•POPC lipoprotein - Lei Zhang; James Song; Yvonne Newhouse; Shengli Zhang; Karl H. Weisgraber; Gang Ren (Journal of Lipid Research, 2010)
Apolipoprotein E (apoE), one of the major protein components of lipoproteins in the peripheral and central nervous systems, regulates cholesterol metabolism through its interaction with members of the low density lipoprotein receptor family. One key to understanding apoE function is determining the structure of lipid-bound forms of apoE. Negative-staining (NS) electron microscopy (EM) is an easy and rapid approach for studying the structure and morphology of lipid-bound forms of apoE. However, an artifact of using the conventional NS protocol is that the apoE•phospholipid particles form rouleaux. In this study, we used cryo-electron microscopy (cryo-EM) to examine apoE4•palmitoyl-oleoylphosphatidylcholine (POPC) particles in a frozen-hydrated native state. By comparing the particle sizes and shapes produced by different NS protocols to those produced by cryo-EM, we propose an optimized protocol to examine apoE4•POPC particles. Statistical analysis demonstrated that the particle sizes differ by less than 5% between the optimized protocol and the cryo-EM method, with similar shapes. The high contrast and fine detail of particle images produced using this optimized protocol lend themselves to the structural study of lipid-bound forms of apoE.